Non-Verbal Communication In Anime "Diamond No Ace" Episodes 1 And 2 (Barthes Semiotics Approach) - Ningrum Tresnasari (IZUMI, 2020)
Non-verbal communication is a communication process where the media used to communicate are body movements or gestures as a form of the depiction of emotions and feelings. Non-verbal communication consists of several types, but in this study, it only focuses on kinesic markers like body movements such as facial expressions, eye contact, hand movements and others. This study aims to describe the types and meanings contained in kinesic attributes in the anime "Diamond no Ace". The research data used are images from anime footage "Diamond no Ace" episode 1 and 2. The research method used is the Barthes semiotic approach. The types of kinesic markers in facial signs include eyes, eyebrows, forehead, cheeks, mouth and teeth, while gestures include hand movements and body postures from head to toe and iconography. Besides, the meaning contained in kinesic markers is divided into the denotative meaning and connotative meaning.